Evaluating the Affective Domain in Al-Islam and Muhammadiyah Learning: Methods, Challenges, and Technology-Based Solutions in Muhammadiyah Schools - Nurul Latifatul Inayati; Intan Dian Saputri (STAI Hubbulwathan Duri, 2025)
The affective domain plays a critical role in shaping students’ character and religious values, especially in Islamic-based educational institutions. In Muhammadiyah schools, Al-Islam and Kemuhammadiyahan (AIK) learning integrates cognitive understanding with affective development. This study aims to explore how the affective domain is evaluated in AIK learning, the challenges encountered, and the potential of technology-based solutions to enhance assessment practices. A qualitative field study was conducted at SMP Muhammadiyah 1 Surakarta using a phenomenological approach. Data were collected through semi-structured interviews with six school stakeholders, non-participant classroom observations, document analysis, and a supporting quantitative survey involving 52 students and 40 parents. Data were analyzed using the Miles and Huberman interactive model, ensuring triangulation across sources. The findings reveal that affective evaluation is primarily conducted through behavioral observation of religious practices and daily interactions, supported by parent-teacher collaboration. The use of e-report systems enables real-time tracking of student character development and fosters transparency with parents. Key challenges include diverse student backgrounds, varying levels of family support, and limited digital literacy among some stakeholders. This study highlights the importance of structured, continuous, and collaborative approaches to affective domain evaluation. Technology, when supported by adequate training and infrastructure, can enhance efficiency and consistency in character assessment. The integration of digital tools and the exploration of artificial intelligence (AI) for affective analysis are recommended for future implementation.